DEVELOPMENT OF CRITICAL THINKING TEST INSTRUMENT READING USING THE GRAPHIC ORGANIZER MEDIA - Otang Kurniaman; Eddy Noviana; Neni Hermita; Dea Sinta Maharani; Ardanil Marwan (JURNAL PAJAR (Pendidikan dan Pengajaran), 2019)
Critical thinking is sensible thinking that focuses on deciding what they should do. This research method uses the 4-D model proposed by Thiagarajan and Semmel with four stages consisting of define, design, development and disseminate. This study only evaluates validators in the value of test instruments with research results assessed by validators about the contents of critical thinking test instruments with an average of 87.5 in the very feasible category, while in the validation results the presentace of critical thinking assessment instruments with an average of 98% in the very decent category. For this reason, it was concluded that the critical thinking test reading instrument with graphic organizer media was appropriate to be used to measure students' abilities in critical thinking